Pemanfaatan Konten Edukatif Di Youtube Untuk Pembelajaran Bahasa Inggris - Rani Dewi Yulyani (Journal on Education, 2024)
To improve students' English language skills, innovative educational content is needed which can increase their interest and understanding of English. A way to improve English language skills is to optimize the use of information technology through various video sharing channels such as YouTube platform. The research was conducted using a qualitative descriptive approach with data collection techniques using questionnaires and interviews. The research results showed that 39 students (40.2%) of YouTube use the YouTube platform several times a week to learn English. Furthermore, it is known that the respondent's assessment criteria for the variable ability to use the internet is at 78.76 with "Good" criteria. The ease variable obtained from learning videos on the YouTube platform had an answer value with "good" criteria. What needs to be done to improve students' ability to obtain learning content on the YouTube platform that is easy to understand and relevant to students' learning needs is to start following English learning channels and create a playlist of learning materials that suit their level and interests, then take advantage of the YouTube Live feature from service providers to interact directly to practice English language skills.